2014
DOI: 10.3389/fphar.2014.00094
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenesis and iron: from epidemiology to cellular level

Abstract: Iron accumulates in human atherosclerotic lesions but whether it is a cause or simply a downstream consequence of the atheroma formation has been an open question for decades. According to the so called “iron hypothesis,” iron is believed to be detrimental for the cardiovascular system, thus promoting atherosclerosis development and progression. Iron, in its catalytically active form, can participate in the generation of reactive oxygen species and induce lipid-peroxidation, triggering endothelial activation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 230 publications
(284 reference statements)
4
114
2
3
Order By: Relevance
“…There is some evidence that with increasing age, high circulating iron levels worsen the atherosclerotic phenotype [9]. Macrophages in the vessel wall can accumulate iron from increased destruction of RBCs or by disturbed iron homeostasis, leading to increased production of ROS and decreased efflux of cholesterol.…”
Section: Clinical Consequences Of Iron Overload In Mdsmentioning
confidence: 99%
“…There is some evidence that with increasing age, high circulating iron levels worsen the atherosclerotic phenotype [9]. Macrophages in the vessel wall can accumulate iron from increased destruction of RBCs or by disturbed iron homeostasis, leading to increased production of ROS and decreased efflux of cholesterol.…”
Section: Clinical Consequences Of Iron Overload In Mdsmentioning
confidence: 99%
“…Despite the large number of studies having been published to date, the role of iron in CVD still generates a fair amount of debate (26). However, the impact of iron on atherosclerosis is still debated.…”
Section: Discussionmentioning
confidence: 99%
“…Iron mediates the oxidative modification of LDL, an important contributing factor to the pathogenesis of atherosclerosis [510] . Cholesterol levels in atherosclerotic lesions correlated with iron deposits [511] , and within the plaque, iron deposition and ferritin induction have been observed in endothelial cells and macrophages in early human lesions, and additionally in VSMCs in late lesions [503] . Interestingly, in hypercholesterolemic pigs, Gerrity [512] found that monocytes were adherent to the lesion areas of aortic endothelium, in endothelial junctions, and in the intima.…”
Section: Atherosclerosismentioning
confidence: 92%
“…According to the "iron hypothesis", iron overload is believed to be detrimental for the cardiovascular system, thus promoting atherosclerosis development and progression [503,504] . Excess of iron generates oxidative stress that hallmarks neurodegenerative diseases and atherosclerosis, a frequent disorder of aging [505] .…”
Section: Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation